Size and geometry effects in notched compact tension specimens. (July 2017) - Horn, A.J.; Sherry, A.H.; Budden, P.J.
Abstract: This paper uses Weibull stress analysis to investigate whether the effective notch toughness K m a t ρ for cleavage fracture measured using Compact Tension (CT) specimens containing a U-notch is dependent on the size and geometry of the CT specimen. Notched CT specimens are typically used to measure a material's effective notch toughness K m a t ρ and to assess failure of a structure containing a non-sharp defect using the Notch Failure Assessment Diagram (NFAD). The paper concludes that K m a t ρ is dependent on specimen thickness B over and above the microstructural weakest link effect arising from differences in the volume of the plastic zone; K m a t ρ is a function of not only the in-plane effect of the notch radius but also an out-of-plane constraint loss which itself is enhanced by the presence of the notch radius. This out-of-plane constraint loss can be more significant than the in-plane effect of the notch radius. The use of experimentally measured K m a t ρ values in an NFAD assessment of a notched structure may therefore be non-conservative if the out-of-plane constraint loss in the CT specimen is more significant than in the structure. For the material considered in this paper, doubling the thickness B of the CT specimen resulted in plane strain conditions being sufficiently dominant to eliminate out-of-plane constraint loss in the CT specimen. Abstract : Effective notch toughness is dependent on both notch radius and specimen thickness. Thickness effect can be more significant than the in-plane effect of notch radius. Failure predictions may be non-conservative if thickness effects not accounted for.